2005
DOI: 10.3171/spi.2005.3.5.0348
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic analysis of ossified ligamentum flavum in a Chinese population

Abstract: Object. The authors performed a retrospective study of clinical and radiological data obtained in 27 Chinese patients with myelopathy induced by ossification of the ligamentum flavum (OLF) who underwent surgery between March 1990 and March 2002. The factors related to surgical outcome of thoracic OLF-induced myelopathy were also assessed. Methods. The preoperative clinical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 26 publications
7
90
1
Order By: Relevance
“…13,19,20,22,33,34,56 Preoperative severity of myelopathy was considered as the most important predictor of the postoperative outcome. 19,20,22,56 In accordance with this finding, our research confirmed that preoperative severity of myelopathy was the most important predictor of the highest postoperative JOA score and the lowest percentage RR in multiple linear regression analyses. In addition, the OLF level (middle thoracic), preoperative duration of symptoms and intramedullary signal change on T2WI were also confirmed and significantly correlated with the surgical outcome by multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,19,20,22,33,34,56 Preoperative severity of myelopathy was considered as the most important predictor of the postoperative outcome. 19,20,22,56 In accordance with this finding, our research confirmed that preoperative severity of myelopathy was the most important predictor of the highest postoperative JOA score and the lowest percentage RR in multiple linear regression analyses. In addition, the OLF level (middle thoracic), preoperative duration of symptoms and intramedullary signal change on T2WI were also confirmed and significantly correlated with the surgical outcome by multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when the ligamentum flavum is replaced by a mature bone, its osseous morphology should be V-shaped or a part of V shape on CT images. 12 Although thoracic OLF has been reported in several Asian countries, such as Japan, [11][12][13][14] China 3,4,[15][16][17][18][19] and South Korea, [20][21][22] and also in Caucasian and Caribbean ethnic groups, [23][24][25][26][27][28] extensive studies on thoracic OLF including a large number of patients have not yet been reported in the literature. This is partly due to the relatively low mean prevalence of thoracic OLF, which was reported as 3.8% in China and as 6.2% for Japanese men and 4.8% for Japanese women.…”
Section: Introductionmentioning
confidence: 99%
“…OLF occurs mainly in the Asian population [2][3][4][5][6][7][8] and there are only a few reports in the Caucasian, African, and Arabic racial groups [9][10][11][12][13][14]. OLF is one of the commonest causes of thoracic spinal stenosis and spinal cord compression, which can cause serious neurological symptoms or even paraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…Kazuhiko Shiokawa et al introduced a 31-case series of middle-aged men who had symptomatic TOLF lesions at a lower thoracic level in 2001 [9]. Shisheng et al reported on 27 patients who had TOLF [7]. All the above-mentioned patients had symptomatic lesions, and all underwent a total laminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…OLF, also known as ossification of the yellow ligament, is a pathological condition that affects the ligament and causes a slow and progressive myeloradiculopathy [1,[7][8][9]. TOLF is rare and usually asymptomatic [1].…”
Section: Discussionmentioning
confidence: 99%